2014
DOI: 10.1159/000365439
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Risk Factors and Hearing Thresholds

Abstract: The objective of this study was to evaluate the influence of atherogenic risk factors on hearing thresholds.In across-sectional study we analyzed data from a Danish survey in 2009-2010 on physical and psychological working conditions. The study included 576 white- and blue-collar workers from children's day care units, financial services and 10 manufacturing trades. Associations between atherogenic risk factors (blood lipids, glycosylated hemoglobin, smoking habits, body mass index (BMI), and ambulatory blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Similar to other studies, we also found that compared with the control group, the TC/HDL ratio, apo B/apo AI ratio and ATH index in SSNHL were higher [10], suggesting the possibility of atherosclerosis in SSNHL patients [21,23]. Apo B/apo AI ratio and ATH index were also found to be favorable predictors of plasma atherosclerosis [15,24].…”
Section: Resultssupporting
confidence: 88%
“…Similar to other studies, we also found that compared with the control group, the TC/HDL ratio, apo B/apo AI ratio and ATH index in SSNHL were higher [10], suggesting the possibility of atherosclerosis in SSNHL patients [21,23]. Apo B/apo AI ratio and ATH index were also found to be favorable predictors of plasma atherosclerosis [15,24].…”
Section: Resultssupporting
confidence: 88%
“…The current results are significant across all PTA thresholds in the overall groups. This contrasts with other studies who have found associations between cardiovascular disease and its risk factors to low‐frequency hearing loss . The proposed mechanism for these results from prior studies suggest microvascular disease leading to ischemic degeneration of the stria vascularis, particularly at the more distal apical parts of the cochlea, causing low‐frequency hearing loss.…”
Section: Discussioncontrasting
confidence: 81%
“…This contrasts with other studies who have found associations between cardiovascular disease and its risk factors to low-frequency hearing loss. 7,10,11,26,27 The proposed mechanism for these results from prior studies suggest microvascular disease leading to ischemic degeneration of the stria vascularis, particularly at the more distal apical parts of the cochlea, causing low-frequency hearing loss. The findings in our study may be due to the differences in the study cohorts and demographics.…”
Section: Discussionmentioning
confidence: 85%
“…This is in accordance with the hypotheses that cardiovascular risk factors affect the whole frequency range. Stronger associations with low-frequency hearing thresholds are found previously for cardiovascular risk factors (Frederiksen et al, 2014;Friedland et al, 2009) and for cardiovascular disease (Gates et al, 1993;Friedland et al, 2009).…”
Section: Frequency Specific Effectsmentioning
confidence: 55%